WHAT MOTIVATES STUDENTS TO WALK IN A HILLY UNIVERSITY CAMPUS? - Walia, Komika; Sarkar, Shuvojit; Dewan, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Walking is a daily activity undertaken by campus users for trips within or outside the campus. Walking purposes are either utilitarian or hedonistic. Walkable campuses are important for the health and wellbeing of its users. This study is part of an on-going research to assess the built environment factors that influence the walkability of a hilly campus and students’ perceptions towards leisure walking in the campus. Case study method is used to study the campus environment and its influence on walkability within the campus. The motivation factors are recreation and transportation which are influenced by weather, distance between facilities, shade and resting places along the walking routes. Findings of this qualitative study provide a preliminary analysis of the user’s perspective about campus walking environment of a hilly terrain.